The impact of insulin resistance and glycaemic control on insulin-like growth factor-1 in patients with type 2 diabetes: a cross-sectional study - Hasanain MohammedHuthaifa AbdlWhab; Araz Al-Saffar; Osama Abbas Mahdi; Rafid Badri Alameri (Clinical Diabetes and Endocrinology)
Abstract Background Type 2 diabetes mellitus (T2DM) is a multifaceted metabolic disorder. Over the past decade, the potential role of Growth Hormone (GH) and Insulin-like Growth Factor-1 (IGF-1) in the pathogenesis and progression of T2DM has garnered scientific interest. These hormones, while interrelated, exert differential effects on glucose homeostasis; GH elevates blood glucose levels, whereas IGF-1 sustains insulin secretion and augments insulin sensitivity. Objective The study aimed to investigate the impact of insulin resistance and glycaemic control on IGF-1 levels and to assess other risk factors influencing IGF-1 in T2DM. Methods A cross-sectional study was conducted at the National Diabetes Centre, Baghdad, Iraq, from May 2020 to May 2021. Sixty patients with T2DM were evaluated for fasting plasma glucose (FPG), GH, IGF-1, HbA1c, HOMA-IR, HOMA-B, and anthropometric measures following a comprehensive history and physical examination, focusing on any variables that could influence their metabolic profile. Patients with Type 1 diabetes mellitus, thyroid disease, pituitary disease, chronic kidney disease, hepatic disease, and pregnancy were excluded from the study. Results Patients with poorly controlled diabetes (HbA1c > 8) exhibited significantly elevated IGF-1 levels compared to those with HbA1c < 8 (166 vs. 134, P = 0.016). The mean IGF-1 was significantly lower in patients with insulin resistance (IR) compared to those without IR (143 vs. 192, P = 0.001), with a significant negative correlation with Body Mass Index (BMI) and a significant positive correlation with HbA1c and Quantitative Insulin Sensitivity Index (QUICKI). Elevated IGF-1 levels were observed with increasing age, duration of T2DM, higher HbA1c, higher QUICKI, and lower BMI. No significant difference was found in IGF-1 values with regards to HOMA-B, fasting insulin, and waist-hip ratio. Conclusion Patients with poorly controlled T2DM exhibit higher IGF-1 levels, while those with obesity and high insulin resistance demonstrate lower IGF-1 levels. Further prospective studies are warranted to evaluate the potential of using IGF-1 to reduce insulin resistance and improve metabolic and glycaemic measures in individuals with T2DM and obesity or insulin resistance.